Readiness Of The Medical Record Unit To Face The Accreditation Process At The Clinic - Harniati Harniati; Abdul Rahman (Journal of Innovative and Creativity, 2025)
RSU Wisata UIT is a health facility in Makassar City that offers first-rate health services to the community, including 4D ultrasound with AI to monitor pregnancy, and serve patients from inside and outside the city. Efforts that can be made to improve the quality and safety of clinical services in primary clinics are through accreditation. The medical record unit is part of the service support unit at the primary clinic which is included in the assessment of the accreditation of the primary clinic. The readiness of the medical record unit needs to be assessed to see what documents and implementation do not yet exist. The identification of the readiness of the accreditation of the medical record unit of Clinic X had been carried out two years earlier, namely in 2021. This study aims to find out how the continuation and readiness of the accreditation of the medical record unit will be in 2024. This research method uses an observational descriptive approach through a cross sectional design. The research data was collected through observation and interviews with medical record officers, then analyzed by comparing the predicted score of the accreditation readiness score of the clinical medical record unit X in 2021 with 2024. The results show that the readiness for accreditation for clinical medical record units X in 2024 has increased, from a predicted score in 2021 of 41.7% to 65.8% in 2024. With the comparison of accreditation readiness, it can be used as evaluation material to meet the needs of both the documentation that has not been ready and the procedures that have never been implemented. From the results of this study, it can be concluded that the achievement of accreditation assessment has not been maximized due to almost all assessment indicators that have not been possessed, including the availability of supporting documents. Clinics that can create a frame of reference first, by determining methods and analyzing instruments that are in accordance with the method used.